Indian Trail - Montgomery, R. A.; Millet, Jason (Waitsfield, Vt. Chooseco, 2007)
You live with your tribe in a pueblo village. There has been no rain for a long time, and the crops you eat are dying. You have heard stories about spirits called kachinas that help people. Kachinas are so powerful they might even be able to change the weather. You must go find the kachinas, and save your village. Should you go alone, or bring friends to help you? The journey will be hard, and you must be brave. You choose what happens next!
Revised version of 1983 publication published by Bantam.
"There are 9 possible endings"--Cover.
90698
Keywords: Plot-your-own stories; Pueblo Indians; Indians of North America -- Southwest, New; Adventure